2022
DOI: 10.3390/cancers14184433
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Human Endogenous Retroviruses at Locus-Specific Resolution in Non-Small Cell Lung Cancer

Abstract: Lung cancer is the second most commonly diagnosed cancer and the leading cause of cancer deaths worldwide. Among its subtypes, lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) are the most common, accounting for more than 85% of lung cancer diagnoses. Despite the incredible efforts and recent advances in lung cancer treatments, patients affected by this condition still have a poor prognosis. Therefore, novel diagnostic biomarkers are needed. Recently, a class of transposable elements called h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Although the importance of miRNAs in cancer is well-defined, and widespread dysregulation of miRNAs have been reported in soft tissue sarcomas 23 , there is much to discover regarding the roles of miRNAs in AS. Previously it has been suggested that miR-210 24 , miR-214 25 , miR-340 26 , and miR-497 27 may elicit tumor-suppressing phenotypes in AS.…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of miRNAs in cancer is well-defined, and widespread dysregulation of miRNAs have been reported in soft tissue sarcomas 23 , there is much to discover regarding the roles of miRNAs in AS. Previously it has been suggested that miR-210 24 , miR-214 25 , miR-340 26 , and miR-497 27 may elicit tumor-suppressing phenotypes in AS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies point out the biological relevance of human endogenous retroviruses (HERVs), a class of transposable elements, in cancer biogenesis and also their potential clinical applications as novel diagnostic, prognostic, and treatment response biomarkers for several tumor types ( 6 19 ). HERVs are remnants of exogenous retroviruses integrated into the human genome during evolution, accounting for 8% of the human genome ( 20 22 ). Indeed, HERVs share genomic similarities with other exogenous retroviruses.…”
mentioning
confidence: 99%
“…Indeed, HERVs share genomic similarities with other exogenous retroviruses. However, due to accumulated mutations, HERVs have preserved the features of their original provirus to a highly variable extent, ranging from the retention of a complete set of long terminal repeats (LTRs) and retroviral genes to the retention of only fragments of the parental viral genomes ( 20 , 21 , 23 ). Based on their sequences, HERVs are usually classified into groups ( 20 , 21 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations